Financial sustainability of oil and gas companies—basis for building resilience strategies - Grosu, Veronica; Tiron-Tudor, Adriana; Socoliuc, Marian; Ciubotariu, Marius-Sorin; Hlaciuc, Elena; Macovei, Anamaria-Geanina; Tulvinschi, Mihaela; Mihalciuc, Camelia-Cătălina; Melega, Anatol (Frontiers in Environmental Science, 2023)
The crisis situations that have affected the oil and gas market have had a significant impact on the companies’ performance from this sector and especially on their customers. In these circumstances, many companies faced increasing difficulties and in some cases, in order to survive, they had to restructure their business or even leave the market. Considering this context, this kind of situations are also manifesting in Romania where we can identify companies facing the erosion of their competitive position, with economic, financial and capital consequences, while other companies still managed to react positively to the crisis generated by the energy sector through innovation and internationalization. This article analyses the sustainability of the operational activity of oil and gas extraction companies from Romania, based on financial and economic data and information, having the aim of investigating the way in which the performance of different markets has influenced the economic and financial results and consequently, the implications of this influence for the structure of the activity and on the financial-economic sustainability. The research methodology is specific to a quantitative research, based on a sample of financial and economic data reported by all 29 oil and gas extraction companies from Romania over the period of 2008-2022. The data collected from the financial reports formed the basis for the calculation of the financial indicators and ratios considered relevant in forecasting the economic and financial sustainability of these companies. The results obtained are materialised in the development of a model whose aim is to assess the financial and economic sustainability, its independent variables being grouped into performance, activity and risk indicators. The usefulness of the results obtained is relevant both for the companies concerned and for their customers and suppliers who will show a visible dependence on energy costs, but also for investors and financiers directly interested in performance and sustainability information, on the basis of which they will determine the value of their own economic benefits.